Remarks on Case 06111-2009-PA/TC: an opportunity to inquire about the Peruvian Church and State System - Mosquera Monelos, Susana (2011)
Last 7th March the Peruvian Constitutional Court made Case 06111-2009-PA/TC public, a very significant judgment that affects the essential content of religious freedom. This paper will deal with the main topics used by the Court: religious freedom, equal treatment, secularism, and collaboration with religious entities. It will also try to offer a wider approach to the Peruvian legal system of Church and State relationship, considering the new law on religious freedom, and some other Constitutional decisions, because it is not completely sure that focus is directed to the correct place.